Specialization course in Neuroscience applied to education: a report of actions developed in a Physical Exercise and Nervous System Class (Research, Society and Development, 2021)
Continuing education courses are important initiatives to facilitate the teacher comprehension about neuroscience. This paper is a report of actions developed in a Physical Exercise and Nervous System class that presented and discussed the physiological responses of physical activity (PA) practice on the Central Nervous System (CNS). The component was offered in two modules. Module I: PA and physiological adaptations; Module II: mechanisms of action of PA on CNS. The students demonstrated excellent engagement in the proposed activities and highlighted the importance of debating about neuroscience applied to Education. We considered a main positive outcome the interest of the students in applying the new knowledge in the schools where they work.